2020
DOI: 10.1186/s40478-020-00927-4
|View full text |Cite
|
Sign up to set email alerts
|

Validation of machine learning models to detect amyloid pathologies across institutions

Abstract: Semi-quantitative scoring schemes like the Consortium to Establish a Registry for Alzheimer's Disease (CERAD) are the most commonly used method in Alzheimer's disease (AD) neuropathology practice. Computational approaches based on machine learning have recently generated quantitative scores for whole slide images (WSIs) that are highly correlated with human derived semi-quantitative scores, such as those of CERAD, for Alzheimer's disease pathology. However, the robustness of such models have yet to be tested i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 41 publications
2
37
0
Order By: Relevance
“…Finally, prospective effectiveness outside this cohort remains open to exploration. Whereas this study was consistent with our earlier work leveraging one expert annotator 14 and its independent application at another institution 15 , we expect larger cohorts and institutionally-diverse datasets will facilitate more comprehensive standards in neuropathology. For instance, performance for CAA with 6E10 was lower than for other stains (Supplementary Figure 4).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Finally, prospective effectiveness outside this cohort remains open to exploration. Whereas this study was consistent with our earlier work leveraging one expert annotator 14 and its independent application at another institution 15 , we expect larger cohorts and institutionally-diverse datasets will facilitate more comprehensive standards in neuropathology. For instance, performance for CAA with 6E10 was lower than for other stains (Supplementary Figure 4).…”
Section: Discussionsupporting
confidence: 89%
“…In previous work, we automated a single expert’s annotations using DL 14 . This approach was validated by independent study with a different cohort 15 . However, individual bias of the expert remained, and it was not yet clear if these methods could scale across multiple experts, institutions, and data modalities—all of which are critical for assessing generalizability.…”
Section: Introductionmentioning
confidence: 99%
“…Because variations in scanning techniques have the possibility of causing biases between local institutions, future development would benefit from crossinstitutional data sources to help validate the generalizability of the algorithm. However, some recent research 42,43 has found that regularized convolutional neural networks trained on single-institution data were robust to cohort variations during validation on data from other institutions.…”
Section: Discussionmentioning
confidence: 99%
“…These approaches are becoming more common in AD research with the increase in available multimodal neuroimaging data to classify AD and predict progression from mild cognitive impairment (MCI) to AD ( 9 ). In neuropathology, deep learning has been recently used to classify and quantify tau pathology ( 10 ) as well as Aβ plaques and cerebral Aβ angiopathy ( 11 , 12 ).…”
Section: Introductionmentioning
confidence: 99%